Time-varying long-term Memory in the Tehran Stock Exchange: the Generalized Hurst Exponents and the Rolling Window Approach - elham farzanegan (Journal of Asset Management and Financing, 2020)
Objective: This study is the first to examine the issue of time-varying long-term memory in the Tehran Stock Exchange, using a new efficiency index through a rolling window technique. To test the robustness of the results, this estimation technique is repeated with time windows with 5-day shifts. Furthermore, the wild bootstrap versions of the Automatic Portmanteau test (AQ) and the Automatic Variance Ratio test (AVR) have been performed with 14- and 5-day shifts. Method: The sample employed in this paper consists of daily observations on the Tehran Stock Exchange Index (TEPIX), covering the period from December 2008 to October 2019, making up a total of 2621 observations. The TEPIX series are collected from the Rahavard Novin software. The hypotheses are analyzed by Excel, EViews, R, and MATLAB software. Results: The findings show that in the Tehran Stock Exchange the estimated values of the generalized Hurst exponents (GHE) for all windows with 14-day shifts are over the efficiency indicator 0/5. Therefore, a kind of long-term memory exists on the Tehran Stock Exchange. Moreover, a high degree of inefficiency ratio is observed in the market. Furthermore, the Tehran Stock Exchange does not become more efficient over time. Finally, the results from the time windows with 5-day shifts as well as wild bootstrap versions of the AQ and AVR tests with 14- and 5-day shifts indicate that the previously-mentioned empirical results are robust. The findings from the study provide important implications for investors, portfolio managers, and policy-makers.